Employability of Mathematics Majors from a State University’s Bachelor of Secondary Education Program - Ubat, Joel; Villalon, Guadiosa; Sapotalo, Cheramae; Sta. Ana, Jessica Ann (Journal of Interdisciplinary Perspectives, 2024)
This study traced the employability of Bachelor of Secondary Education, Major in Mathematics Graduates of a Philippine state university. One hundred respondents were surveyed using a questionnaire distributed via Google Forms, patterned after the Commission on Higher Education's (CHED) standardized form. The descriptive research design was employed to assess the employment status of the graduates. Among the respondents, 47% are currently employed in government, 34% in private organizations, and 42% are teachers. Additionally, 46% hold permanent positions with an average salary between 20,000 and 30,000 PHP. The study recommends enhancing students' skills in Mathematics, encouraging continuous education to improve their ranking, and seeking diverse job experiences to broaden career opportunities.